Knowing Me, Imagining You: Projection and Overbidding in Auctions - Yves Breitmoser (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2017)
Overbidding in auctions has been attributed to e.g. risk aversion, loser regret, level-k, and cursedness, relying on varying identifying assumptions. I argue that ẗype projection\'örganizes these findings and largely captures observed behavior. Type projection formally models that people tend to believe others have object values similar to their own - a robust psychological phenomenon that naturally applies to auctions. First, I show that type projection generates the main behavioral phenomena observed in auctions, including increased sense of competition (l̈oser regret\") and broken Bayesian updating (c̈ursedness\"). Second, re-analyzing data from seven experiments, I show that type projection explains the stylized facts of behavior across private and common value auctions. Third, in a structural analysis relaxing the identifying assumptions made in earlier studies, type projection consistently captures behavior best, in-sample and out-of-sample. The results reconcile bidding patterns across conditions and have implications for behavioral and empirical analyses as well as policy.
Keywords: C72; C91; D44; 330; auctions; overbidding; projection; risk aversion; cursed equilibrium; depth of reasoning